2018
DOI: 10.1002/jcb.28257
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of stanniocalcin‐1 inhibits the development of osteoarthritis by inhibiting survival and inflammation of fibroblast‐like synovial cells

Abstract: Objective Osteoarthritis (OA) is a progressive and disabling disorder, characterized by synovial inflammation and joint effusion. This study aimed to explore the role of stanniocalcin-1 (STC1) in the development of OA by regulating the survival and inflammation of fibroblast-like synovial (FLS) cells.Methods Microarray analyses were adopted to screen differentially expressed genes (DEGs) related to OA, and regulatory microRNA (miR) was also identified. Synovial tissue samples from patients with OA and healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 37 publications
0
16
0
1
Order By: Relevance
“…Other than that, several studies showed increased MMP-3 in osteoarthritis [47,48,53,73,78,82,83]. The induction of MMP-3 has been related to miR-149 and miR-454 expression in osteoarthritis [51,84].…”
Section: The Role Of Matrix Metalloproteinases (Mmps) In Osteoarthritismentioning
confidence: 98%
See 4 more Smart Citations
“…Other than that, several studies showed increased MMP-3 in osteoarthritis [47,48,53,73,78,82,83]. The induction of MMP-3 has been related to miR-149 and miR-454 expression in osteoarthritis [51,84].…”
Section: The Role Of Matrix Metalloproteinases (Mmps) In Osteoarthritismentioning
confidence: 98%
“…Conversely, overexpression of IL-37 in chondrocytes decreased the MMP-13 level [53]. Two separate studies by Zhang et al and Wu et al showed that changes in microribonucleic acid (miRNA) expression in osteoarthritis could alter the MMP-13 level [35,51]. They found that miR-502-5p and miR-454 enhanced the MMP-13 level.…”
Section: The Role Of Matrix Metalloproteinases (Mmps) In Osteoarthritismentioning
confidence: 99%
See 3 more Smart Citations